Pemenuhan Hak Politik Narapidana dalam Pilkada 2024 di Lapas Kelas II A Kota Kupang - Gabriella Vanesa Mamoh; Josef Mario Monteiro; Marlyani Anita Seran (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aimed to analyze the fulfillment of prisoners' political rights in the 2024 Regional Head Election (Pilkada) at Class IIA Kupang Correctional Institution and to identify the factors affecting its implementation. The study employed an empirical juridical method using a descriptive approach. Data were collected through interviews with officials of the Class IIA Kupang Correctional Institution and the General Election Commission (KPU) of Kupang City, supported by a review of relevant legislation and legal literature. The findings indicate that the fulfillment of prisoners' political rights has been facilitated through the establishment of special polling stations, voter registration and updating, and coordination between correctional authorities and election administrators. However, the implementation has not been fully optimal due to several administrative constraints, including anomalies in the National Identity Number (NIK), incomplete voter transfer administration (Form A5), inmates who were still administratively registered as active members of the Indonesian National Armed Forces or Police, and newly admitted inmates close to election day. These findings suggest that the effective protection of prisoners' political rights depends not only on legal guarantees but also on accurate population administration and effective inter-agency coordination in updating voter data.